Case of bacterial endophthalmitis caused by an Agrobacterium radiobacter-like organism. - Miller, J M (1996)
A case of postsurgical endophthalmitis caused by Agrobacterium radiobacter in a 70-year-old male is reported. A. radiobacter organisms are normally environmental bacteria but may occasionally be opportunistic pathogens. Infection in this case occurred after the patient was discharged following routine cataract surgery. The infection cleared after empiric therapy intraocular administration of vancomycin and gentamicin.